Effect of Ginger Extract as a Natural Tenderizer in Spent Hen Meat : 10.5958/2581-6616.2020.00008.0 - Rovida, Mir; Wani, Sarfaraz A.; Ahmad, Sheikh Rafeh; Sofi, Asif H.; Khan, Azmat A.; Hussain , Ishraq; Rather, Mudasir A. (Journal of Meat Science, 2021)
Aqueous extract of ginger (Zingiber officinale) was investigated for its effect as a natural tenderizing agent in thigh meat obtained from spent hens of commercial layer stock. The thigh portion obtained after slaughter and dressing of spent hens were treated with five treat ment solutions viz. 0.2% papain as positive control (T1), naive control without any treatment (T2); 2% Ginger Extract (T3); 4% Ginger Extract (T4); and 6% Ginger Extract (T5). The samples were kept for 24 hours at 4oC and then divided into two groups. One group of samples was analyzed for various physico-chemical, tenderizing and sensory parameters to ascertain the effect of the Ginger Extract. The results revealed that with increasing Ginger Extract level, there was an increase in pH, moisture content and water holding capacity while as decrease in hydroxyproline content and collagen content, thereby decreasing the toughness and thus desirably improving the tenderness of spent hen meat. Ginger Extract also improved sensory parameters like appearance, flavor, tenderness, juiciness and overall acceptability scores. The other group of samples was cooked for 35 minutes in 1.5 % salt solution. Ginger Extract increased the product yield, pH and moisture content and decreased the shear force value in cooked samples. Ginger Extract also imparted better appearance, color and tenderness scores in cooked samples. Although all levels of Ginger Extract improved the quality of meat, however, the best results were found for 6% Ginger Extract. It was concluded that ginger is a potential natural tenderizer and can thus be explored for its role in the meat processing industry to improve the overall quality of otherwise less valued tougher spent hen meat.